1996
DOI: 10.1002/(sici)1097-0215(19960703)67:1<63::aid-ijc12>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and pancreas cancer: A case-control study of the search programme of the IARC

Abstract: A multi-centre case-control study of pancreas cancer, designed to be population-based, to use a random sample of local populations as controls and to use a common protocol and core questionnaire, was conducted as the first study of the SEARCH programme of the International Agency for Research on Cancer. "Ever-smokers'' were found to be at increased risk for pancreas cancer compared with "never-smokers" consistently in all strata of gender, response status and centre. Risk of pancreas cancer was found to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 31 publications
(20 reference statements)
2
55
0
2
Order By: Relevance
“…18,19,41,42 To date, several cohort studies have consistently reported that cigarette smoking increases the risk of pancreatic cancer. [34][35][36][37][38][39][40] Compared with case-control studies, 9,10,[18][19][20] however, the strength of the association was relatively weak in these cohort studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19,41,42 To date, several cohort studies have consistently reported that cigarette smoking increases the risk of pancreatic cancer. [34][35][36][37][38][39][40] Compared with case-control studies, 9,10,[18][19][20] however, the strength of the association was relatively weak in these cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…30 Epidemiological studies from European countries and the United States have consistently shown that cigarette smoking is associated with an increased risk of pancreatic cancer, but the dose-response relationship has not been clear due to inconsistent findings among these studies. [18][19][20][21][22][23][31][32][33][34][35][36][37][38][39][40][41][42] In addition, recent observational studies have provided consistent evidence for an association of diabetes with increased risk of pancreatic cancer. [27][28][29] To date, however, very few studies have analyzed the potential interaction between smoking and other risk factors, in terms of manifestations of pancreatic cancer.…”
mentioning
confidence: 99%
“…A known risk factor for pancreatic cancer is smoking, which increases the risk two-to three-fold. 4 Also, patients with chronic pancreatitis have increased risk for developing pancreatic carcinoma. 5,6 Coexpression of several members of the matrix metalloproteinase (MMP) family is characteristic of human malignant tumors.…”
mentioning
confidence: 99%
“…1 Smoking is the most important and most consistent environmental risk factor for pancreatic cancer; the risk is increased roughly 3-fold for men and women with heavy cigarette consumption. 2,3 Several dietary factors have been reported to be protective, including fresh fruits and vegetables, dietary fibre and vitamin C. 4,5 Other foods have been reported to increase the cancer risk, including salted and smoked foods, fried foods and refined sugar. 5 It is clear that familial factors are also involved in susceptibility to pancreatic cancer.…”
mentioning
confidence: 99%